Early Cytoskeletal Protein Modifications Precede Overt Structural Degeneration in the DBA/2J Mouse Model of Glaucoma - Wilson, Gina N.; Smith, Matthew A.; Inman, Denise M.; Dengler-Crish, Christine M.; Crish, Samuel D. (Frontiers in Neuroscience, 2016)
Axonal transport deficits precede structural loss in glaucoma and other neurodegenerations. Impairments in structural support, including modified cytoskeletal proteins and microtubule-destabilizing elements, could be initiating factors in glaucoma pathogenesis. We investigated the time course of changes in protein levels and post-translational modifications in the DBA/2J mouse model of glaucoma. Using anterograde tract tracing of the retinal projection, we assessed major cytoskeletal and transported elements as a function of transport integrity in different stages of pathological progression. Using capillary-based electrophoresis, single- and multiplex immunosorbent assays, and immunofluorescence, we quantified hyperphosphorylated neurofilament-heavy chain, phosphorylated tau (ptau), calpain-mediated spectrin breakdown product (145/150kDa), β –tubulin, and amyloid-β42 proteins based on age and transport outcome to the superior colliculus (SC, the main retinal target in mice). Phosphorylated neurofilament-heavy chain (pNF-H) was elevated within the optic nerve (ON) and SC of 8-10 month-old DBA/2J mice, but was not evident in the retina until 12-15 months, suggesting that cytoskeletal modifications first appear in the distal retinal projection. As expected, higher pNF-H levels in the SC and retina were correlated with axonal transport deficits. Elevations in hyperphosphorylated tau (ptau) occurred in ON and SC between 3-8 month of age while retinal ptau accumulations occurred at 12-15 months in DBA/2J mice. In vitro co-immunoprecipitation experiments suggested increased affinity of ptau for the retrograde motor complex protein, dynactin. We observed a transport-related decrease of β-tubulin in ON of 10-12 month-old DBA/2J mice, suggesting destabilized microtubule array. Elevations in calpain-mediated spectrin breakdown product were seen in ON and SC at the earliest age examined, well before axonal transport loss is evident. Finally, transport-independent elevations of amyloid-β42, unlike pNF-H or ptau, occurred first in the retina of DBA/2J mice, and then progressed to SC. These data demonstrate distal-to-proximal progression of cytoskeletal modifications in the progression of glaucoma, with many of these changes occurring prior to complete loss of functional transport and axon degeneration. The earliest changes, such as elevated spectrin breakdown and amyloid-β levels, may make retinal ganglion cells susceptible to future stressors. As such, targeting modification of the axonal cytoskeleton in glaucoma may provide unique opportunities to slow disease progression.